EMPLOYEE ENGAGEMENT OF AN OUTSOURCING COMPANY IN BANGKOK NOI DISTRICT, BANGKOK - อำนวยผล, ปุณยนุช (Pathumthani University Academic Journal, 2020)
This research is a qualitative research which applied phenomenology research as the research strategy. The objective is to study the current situations and problems with the employee engagement of an outsourcing company in Bangkok Noi District, Bangkok. The data collection in this study using semi-structured interview by pilot study with 10 participants with supervisors and administrative officers obtained by using the Criterion Sampling method And using In-depth Interview Then transcribe the interview Word-by-word comes out as a document (Transcription). Data analysis by using ATLAS.ti software. The preliminary found that 3 Part, 1: Working relation problems includes 1) Not familiar with coworkers, 2) Cannot get along with supervisors, 3) Do not understand their work assignment, 2: Management style problems includes 1) Compare themselves with permanent staff, 2) Lower income and welfare, 3) Overtime in day-off, And 3: Personal problems includes 1) Work behavior and attitudes, 2) Need more time for continuous education, 3) Family problems, 4) Not enough income.